Inovasi Pembelajaran Bahasa Indonesia Dalam Kurikulum Merdeka Belajar Untuk Mewujudkan Profil Pelajar Pancasila - Sri Sumaryamti (Jurnal Indonesia Sosial Teknologi, 2023)
— Innovation in Indonesian Language Learning through the independent learning curriculum to create a Pancasila student profile. Nowadays there are still many teachers who use theoretical and rote learning techniques, so that learning activities tend to be stiff, monotonous, and boring. Especially in Indonesian language lessons, the material presented is in fact still not able to stick to students as something rational, cognitive, and affective. It is the use of conventional learning methods that has an impact on the level of mastery of the subject matter Indonesian students who are still low. Furthermore, this kind of learning condition is a form of student failure in developinglanguage knowledge and skills, as well as a positive attitude towards the good and correct use of the Indonesian language. Conditions like this can be overcome by implementing learning innovations that can be used by teachers in implementing Indonesian language learning through various approaches, which are contained in four aspects of Indonesian language skills, namely listening, speaking, reading and writing skills.